2009
DOI: 10.1002/mabi.200900005
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Subtilisin A onto Thin Films of Maleic Anhydride Copolymers

Abstract: Enzymes cleaving the biopolymer adhesives of fouling organisms are attracting attention for the prevention of biofouling. We report a versatile and robust method to confine the serine protease Subtilisin A (or Subtilisin Carlsberg) to surfaces to be protected against biofouling. The approach consists of the covalent immobilization of the protease onto maleic anhydride copolymer thin film coatings. High-swelling poly(ethylene-alt-maleic anhydride) (PEMA) copolymer layers permitted significantly higher enzyme lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Recently, we have developed a well-defined model system to investigate the influence of immobilized subtilisin A on the adhesion of major marine foulers (Tasso et al 2009a;Tasso et al 2009b). Our studies showed that the adhesion strength of Ulva linza spores and Navicula perminuta cells decreased in the presence of the active enzyme, and that the effect of the enzyme was significantly enhanced when the enzyme was surfaceconfined (Tasso et al 2009b), revealing the important role of enzyme location at the surface-fouler interface on antifouling efficacy.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Recently, we have developed a well-defined model system to investigate the influence of immobilized subtilisin A on the adhesion of major marine foulers (Tasso et al 2009a;Tasso et al 2009b). Our studies showed that the adhesion strength of Ulva linza spores and Navicula perminuta cells decreased in the presence of the active enzyme, and that the effect of the enzyme was significantly enhanced when the enzyme was surfaceconfined (Tasso et al 2009b), revealing the important role of enzyme location at the surface-fouler interface on antifouling efficacy.…”
Section: Introductionmentioning
confidence: 89%
“…Reactive immobilization of enzymes onto MA copolymer films was achieved by exposing the copolymer layers to enzyme solutions of variable concentration, as described in Tasso et al 2009a). …”
Section: Preparation Of Bioactive Layersmentioning
confidence: 99%
See 3 more Smart Citations